Tree storage of Nagpur mandarin (Citrus reticulata) fruits by managing incidence of creasing disorder in central India (Current Horticulture, 2024)
An experiment was conducted to improve the yield and quality of Nagpur mandarin (Citrus reticulata Blanco) at ICAR-CCRI, Nagpur, during 2020.The pre-harvest foliar application of 20 or 25 ppm of GA3 along with 1.5% urea delays the senescence of tissues and makes albedo tissues compact which helps in increasing the yield by delayed harvesting, improving the quality of fruits by maintaining their firmness. The yield and yield attributes, viz. maximum yield per plant and total estimated yield per hectare was noted in GA3 20 ppm + urea 1.5% (130.73 kg/plant and 36.21t/ha) in ambia bahar and in GA3 25 ppm + urea 1.5% (82.48 kg/plant and 22.84 t/ha) in mrig bahar. Minimum number of creased fruits recorded in GA3 25 ppm + urea 1.5%in both the seasons (38 in ambia bahar and 19 in mrig bahar). Maximum fruit firmness (2.33 kg/cm2) recorded in GA3 25 ppm + urea 1.5% in ambia bahar and in GA3 20 ppm + urea 1.5% (2.65 kg/cm2) in mrig bahar indicating fruits are less matured compared to other treatments. Fruit physical characteristics, viz. maximum fruit weight and volume were recorded in GA3 20 ppm + urea 1.5% (162.70 g and 159.50 cm3 respectively) in ambia bahar and in GA3 25 ppm + urea 1.5% (146.25g and 144.00 cm3 respectively) in mrig bahar over the control. The biochemical characteristics, viz. highest TSS was recorded in the control in both ambia and mrig bahar (10.10% and 11.97% respectively) indicating that fruits were ripen earlier compared to the fruits of other treatments, whereas lowest TSS (8.92%) was recorded in GA3 20 ppm + urea 1.5% in ambia bahar and in GA3 25 ppm + urea 1.5% (9.92%) in mrig bahar shown delayed ripening of the fruits. Maximum acidity was noted in GA3 25 ppm + urea 1.5% in both ambia and mrig bahar (0.89% and 0.84% respectively) compared to other treatments.
Keywords: Tree storage; Incidence; Disorder; Albedo; Cracks